Non-compliance to diet and medication among type 2 diabetes mellitus patients in selected hospitals of Kathmandu. - Kafle,Nisha Kusum (2017)
SUMMARY: Diabetes Mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The chronic hyperglycemia of diabetes is associated with failure of different organs, especially the eyes, kidneys, nerves, heart, and blood vessels. Type 2 diabetes is the most common form of Diabetes Mellitus (95%) in which body cannot use insulin properly. Compliance to diet and medication is defined as an extent to which a person's behavior in terms of taking medications and following diets coincides with the healthcare provider's recommendations for health and medical advice. Non compliance is defined as those who do not properly follow those recommendations. Diabetes has become a major public health problem globally affecting people of all ages. Non compliance severely compromises the effectiveness of treatment and adversely affects the patient's condition. Therefore, increasing compliance to medication and diet is of paramount importance. The main purpose of this study is to assess and compare the proportion of non-compliance to diet and medication of type 2 diabetes mellitus patient between public and private hospitals in Kathmandu valley. A Descriptive cross-sectional and quantative study was designed and conducted among 182 type 2 diabetes mellitus patients age more than 16 years and diagnosed for at least 6 months from two public and two private hospitals/diabetic clinics in Kathmandu valley by using purposive sampling. Data were collected through face to face interview by using semi structured questionnaire. Socio-demographic, behavioral risk factors, medication compliance and dietary compliance related information were collected. Epidata version 3.1 was used for data entry and International Business Machine Stastical Package for Social Science (IBMSPSS) version 21 was used for analysis. Chi- squared tests was used as a test of significance. Odds ratio (OR) and the corresponding 95% confidence intervals (CI) were calculated. A 2 sided P-value <0.05 was considered significant. Mean age of the respondents was 54.67 with Standard deviation (SD) ±11.69, where 53.3% were males. Janajati (36.8 %) was the major ethnic group. Almost 89% of the respondents were married and majority of the respondents (85.2%) were from the city/municipality, 39% of the respondents did not have any formal education. More than half (56%) of the respondents were diagnosed for less than 5 years and only 35.7% of the respondents had family history of diabetes. 14.8% respondents were current smoker, 40.1% ever smoker and 59.9% of the respondents never smoked, whereas 19% of the respondents were current drinkers, 41.2% were ever drinkers and 58.8% were never drinkers. Among 182 respondents in the study, majority (41.2%) of the respondents were poor compliant to the medication, 30.8% were high compliant and 28% were non compliant. For the dietary practices majority (79.1%) of the respondents were poor compliant, 12.1% were non compliant and 8.8% were high compliant. Level of education and place of treatment was associated with dietary non-compliance. People who seek medical care in public hospital had 4.89 times more chance of being non compliant to dietary advice then those who seek care in private hospitals and illiterate people have 10.94 times more likely to be dietary non compliant than literate. Education and occupation were the associated factor for medication non-compliance. Illiterate people have 4.32 times more likely to be non compliant to medical advice than literate and self employed respondents were 2.93 times more likely to be non compliant to medical advice than job holder respondents. This study shows that dietary non compliance was more in public hospitals as compared to private hospitals. There should be an improvement in patients counseling, increase access to the dietary guideline with labeled available calories in each packed food. Key words: Type 2 Diabetes, Noncompliance, public and private hospitals.